2021
DOI: 10.1002/ps.6725
|View full text |Cite
|
Sign up to set email alerts
|

Optimization and field evaluation of sex‐pheromone of potato tuber moth, Phthorimaea operculella Zeller (Lepidoptera: Gelechiidae)

Abstract: BACKGROUND The potato tuber moth, Phthorimaea operculella is a key pest of potato and tobacco in China. We compared the sex pheromone titers released by P. operculella female, and the electroantennogram (EAG) responses of male antennae to pheromone compounds under laboratory conditions. Then, the optimal sex pheromone ratio was screened in the field. RESULTS The P. operculella sex pheromone feeding on potato or tobacco was extracted by solvent‐extraction method. Main sex pheromone compounds including E4, Z7‐13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…This approach has previously yielded success in developing pheromone lures for various pest species. 14,16,[38][39][40] In this study, the pheromone ratio was established based on the reasonable quantities of Z7-12:OAc and Z9-14:OAc loaded into each septum. This approach has merit in terms of standardizing and commercializing insect attractants, because previous studies have confirmed the highly consistent proportion of moth pheromones released from rubber septa compared with the amount loaded.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This approach has previously yielded success in developing pheromone lures for various pest species. 14,16,[38][39][40] In this study, the pheromone ratio was established based on the reasonable quantities of Z7-12:OAc and Z9-14:OAc loaded into each septum. This approach has merit in terms of standardizing and commercializing insect attractants, because previous studies have confirmed the highly consistent proportion of moth pheromones released from rubber septa compared with the amount loaded.…”
Section: Discussionmentioning
confidence: 99%
“…Virgin female moths (3 days old) were used to collect sex pheromones at the 7–8 h of scotophase. The sex pheromone glands were extruded by gently pressing the abdomen of virgin females and excised using surgical scissors 13,14 . Fifty glands were collected and immersed in 500 μL of hexane for 20 min, and the gland extract was filtered and stored at −20 °C for subsequent pheromone analysis and wind tunnel bioassays.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…7 The pheromones can play a role in monitoring, interfering with mating and trapping in the control of S. litura and other field crop pests. 8,9 However, the instability of semiochemicals has limited their development speed in the pest control market, so the technical route of related products has focused on the invention of sustained-release carriers. In the research into pheromone carriers, the passive dispenser, comprising a rubber stopper and plastic tube, offers good practical value and economy.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, a wide range of synthetic acaricides is continuously used for their management, which not only poses a threat to non-target organisms and human health, but produces resistance to many acaricides (Elzen 2001, Alsendi et al 2018, Dana et al 2018). In order to minimize the use of chemical acaricides, it is imperative to explore an alternative approach for population prediction and management of pest mites (Yan et al 2022). Host-plant resistance can affect phytophagous pests' growth and development as well as enhance the diversity of natural enemies, hence considered one of the most effective and perdurable approaches in integrated pest management (IPM) systems (Follett 2017, Zhang et al 2022a).…”
Section: Introductionmentioning
confidence: 99%